Institutional reforms in Indian irrigation - Gulati, Ashok; Meinzen-Dick, Ruth S.; Raju, K. Vengama (International Food Policy Research Institute, 2005)
Irrigation is critical to food security and economic growth in contemporary India. The performance of irrigation systems is of serious concern to farmers who rely on them for their crops and livelihoods and to governments that have invested heavily in their development. The most severe problems facing Indian irrigation systems are the increasing costs of new schemes, the huge backlog of incomplete schemes, and the increasing neglect of existing systems. Large-scale canal irrigation systems, in particular, are in poor condition: they are not properly maintained, operations are inadequate, water supplies do not reach the end of systems, and the timing of water supply is unreliable. The wide gap between actual and desirable performance threatens the sustainability of irrigated agriculture. How did this state of affairs come to pass?....[The authors conclude that] more than just structural changes are necessary to achieve adequate reform and improve the performance and long-term sustainability of irrigation systems. Changes in attitudes are also required in how government agencies view farmers and how farmers depend on the government.